Предмет: Математика,
автор: mmaatt
5,6-3(2-0,4x)=0,4(4x+1)
Ответы
Автор ответа:
0
1,2х-1,6х=0,4-5,6+6
-0,4х=0,8
х=-2
-0,4х=0,8
х=-2
Автор ответа:
0
5,6-6+1,2х=1,6х+0,4
1,2х-1,6х=0,4-5,6+6
-0,4х=0,8
х=0,8:(-0,4)
х=-2
Проверка:
5,6-3(2-0,4·(-2))=1,6·(-2)+0,4
5,6-3(2+0,8)=-3,2+0,4
5,6-3·2,8=-2,8
5,6-8,4=-2,8
-2,8=-2,8
1,2х-1,6х=0,4-5,6+6
-0,4х=0,8
х=0,8:(-0,4)
х=-2
Проверка:
5,6-3(2-0,4·(-2))=1,6·(-2)+0,4
5,6-3(2+0,8)=-3,2+0,4
5,6-3·2,8=-2,8
5,6-8,4=-2,8
-2,8=-2,8
Похожие вопросы
Предмет: Алгебра,
автор: oleksandrhomacuk99
Предмет: Математика,
автор: Fbvrtbjf
Предмет: Химия,
автор: belozerovpavel319
Предмет: Математика,
автор: lenasorokina81
Предмет: Алгебра,
автор: vika6867